Local Agenda 21 in Germany: An inter- and intranational comparison - Kristine Kern; Claudia Koll; Malte Schophaus (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2004)
More than ten years after the Rio Earth Summit in 1992, which marked the institutionalization of Agenda 21 and the beginning of Local Agenda 21 processes all over the world, it is time to summarize and evaluate the situation with respect to Local Agenda 21 in Germany. Even in Germany, which can be considered as a latecomer regarding the implementation of Local Agenda 21, the diffusion of this policy innovation seems to have reached its end. This paper starts from an international, comparative perspective and Germany's position as a latecomer regarding Local Agenda 21 initiation; however, it focuses primarily on the intranational, comparative standpoint. We analyze the diffusion of Local Agenda 21 in four German states (Länder) (Berlin, North Rhine-Westphalia, Bavaria, and Thuringia). The comparisons between Germany and other countries at international level and between the Länder at national level demonstrate that the diffusion of Local Agenda 21 depends above all on three factors: (1) local authorities' capacities for action; (2) financial and political support from national and regional governmental organizations; and (3) (trans)national and regional agenda transfer institutions which facilitate the exchange of knowledge and know-how between local authorities, and thus accelerate the diffusion of Local Agenda 21 processes. Local authorities, which have greater capacities for action, which are better supported by the particular German state (Land) where they are located, and which show a higher degree of integration into transfer networks are more active and innovative in the area of Local Agenda 21. – – Mehr als zehn Jahre nach dem Umweltgipfel in Rio 1992, der die Institutionalisierung der Agenda 21 und den Beginn von Lokalen Agenda 21-Prozessen überall in der Welt kennzeichnete, ist es an der Zeit, die Situation der Lokalen Agenda 21 in Deutschland zu bilanzieren und zu evaluieren. Sogar in Deutschland, das als Nachzügler im Bereich der Implementation der Lokalen Agenda 21 betrachtet werden kann, scheint die Diffusion dieser Politikinnovation an ihrem Ende angelangt zu sein. Als Ausgangspunkt dieses Artikels dient die international vergleichende Perspektive und Deutschlands Position als Nachzügler im Hinblick auf die Initiierung der Lokalen Agenda 21. Die Analyse konzentriert sich allerdings vor allem auf die intranational vergleichende Perspektive. Wir analysieren die Diffusion der Lokalen Agenda 21 in vier ausgewählten deutschen Ländern (Berlin, Nordrhein- Westfalen, Bayern und Thüringen). Die Vergleiche zwischen Deutschland und anderen Ländern auf der internationalen Ebene und zwischen den deutschen Ländern auf der nationalen Ebene zeigen, dass die Diffusion der Lokalen Agenda 21 vor allem von drei Faktoren abhängt: (1) den Handlungskapazitäten der Städte und Gemeinden, (2) der finanziellen und politischen Unterstützung durch nationale und regionale Regierungsorganisationen sowie (3) den (trans)nationalen und regionalen Institutionen des Agenda-Transfers, die den Erfahrungsaustausch zwischen den Kommunen verbessern und die Diffusion von Lokalen Agenda 21- Prozessen beschleunigen. Städte und Gemeinden, die über mehr Handlungskapazitäten verfügen, von dem Bundesland, in dem sie liegen, besser unterstützt werden, und einen höheren Grad der Integration in Transfernetzwerke aufweisen, sind im Bereich der Lokalen Agenda 21 aktiver und innovativer.
Keywords: 300